Effect of Place of Incorporation, Chinese Culture, and Business Practices on Corporate Fraud: Evidence from Hong Kong Listed Companies1. (29th April 2017) - Pang, Josephine Chui‐ling; Lo, Simon Ming‐sum
Abstract: Mainland Chinese companies make up more than 50% of the Hong Kong securities market in terms of number of listings and market capitalization. Our empirical results indicate that Chinese companies have a higher incidence of corporate fraud and greater fraud severity than other listed counterparts, even after controlling for state versus private ownership, internal corporate governance, financial standing, firm characteristics, and time factors. Further investigation reveals that incorporation in China and Chinese culture and business practices are two distinct and major driving factors in corporate fraud. Conventional explanatory variables for corporate fraud other than board tenure, firm size, listing year, and year of fraud detection do not have explanatory power in the Hong Kong context.